Mind the gap: the presence of capital and power in the female athlete-male -coach relationship within elite rowing - de Haan, D.; Norman, L. (Sports Coaching Review, 2020)
We draw on Bourdieu`s concept of habitus, capital and field, and Foucault`s understanding of power, to examine how gender as a relation of power is exercised in the female-athlete, male-coach relationship. We conducted in-depth semi-structured interviews with nine international male coaches and female athletes. Our findings reveal a hierarchy within rowing and a perpetuation of the gendering of coaching creating a habitus which positions female athletes below male athletes. The positioning of female athletes effects how capital is defined, used and negotiated by the coaches and athletes. The implications of which need to be addressed by sporting federations in order to support and develop coaches as gender-responsive practitioners, thereby addressing the capital and power gap which is often present in elite sport.